Just and unjust securitization of migration: a comparative analysis of migration to Poland from MENA countries and Ukraine - Polko, Paulina (Frontiers in Political Science, 2025)
Much research confirms that the country of origin of migrants (refugees), as well as their religion, determines the approach of the destination country society to newcomers. It affects the conditions of receiving the acceptance of a legal stay and possible support. Double standards are the main results of this intersection. The study aimed to present the research results on the securitization processes implemented in Poland as a response to two migration crises related to the influx of migrants and refugees from MENA countries and Ukraine. Proposed by Rita Floyd, a just and unjust securitization approach has been implemented in the analysis of securitization movements undertaken by Polish governments in 2015–2023. Critical discourse analysis (CDA) has been used to analyze securitization done by politicians in response to expectations of the society. The results confirm that although in the case of both described influx of securitization of migrants has been implemented, not in all cases it was a response to an existential threat. Migration from MENA countries was securitized much more often than from Ukraine and, at the same time, in most cases, it was unjust securitization. Those results confirm that the country of origin determines the securitization process as well as their justification.